A nonstop variant in REEP1 causes peripheral neuropathy by unmasking a 3′UTR‐encoded, aggregation‐inducing motif. Issue 2 (27th November 2017) - Bock, Andrea S.; Günther, Sven; Mohr, Julia; Goldberg, Lisa V.; Jahic, Amir; Klisch, Cornelia; Hübner, Christian A.; Biskup, Saskia; Beetz, Christian
Abstract: Single‐nucleotide variants that abolish the stop codon ("nonstop" alterations) are a unique type of substitution in genomic DNA. Whether they confer instability of the mutant mRNA or result in expression of a C‐terminally extended protein depends on the absence or presence of a downstream in‐frame stop codon, respectively. Of the predicted protein extensions, only few have been functionally characterized. In a family with autosomal dominant Charcot‐Marie‐Tooth disease type 2, that is, an axonopathy affecting sensory neurons as well as lower motor neurons, we identified a heterozygous nonstop variant in REEP1 . Mutations in this gene have classically been associated with the upper motor neuron disorder hereditary spastic paraplegia (HSP). We show that the C‐terminal extension resulting from the nonstop variant triggers self‐aggregation of REEP1 and of several reporters. Our findings support the recently proposed concept of 3′UTR‐encoded "cryptic amyloidogenic elements." Together with a previous report on an aggregation‐prone REEP1 deletion variant in distal hereditary motor neuropathy, they also suggest that toxic gain of REEP1 function, rather than loss‐of‐function as relevant for HSP, specifically affects lower motor neurons. A search for similar correlations between genotype, phenotype, and effect of mutant protein may help to explain the wide clinical spectra also in other genetically determined disorders. Abstract : Loss‐of‐function variants in REEP1 cause an axonopathy that affects upper motor neurons (A). We identified a REEP1 nonstop variant ("stop loss") in patients with an axonopathy that affects lower motor neurons (B). In silico and in vitro analyses suggested that the resulting 3'UTR‐encoded C‐terminal protein extension (blue) mediates self‐aggregation of mutant REEP1, and thereby likely acts via a gain‐of‐function mechanism.